Diabetes Self-Care Behaviors and Barriers to Clinical Care During COVID-19 Pandemic for Marshallese Adults. Issue 1 (February 2022) - Purvis, Rachel S.; Moore, Ramey A.; Ayers, Britni L.; Felix, Holly C.; Riklon, Sheldon; Andersen, Jennifer A.; Hudson, Jonell S.; O'Connor, Gail; Kelen, Meetu; Heely-Rolston, Lee-Ann Noelani; Shields, Xochitl; McElfish, Pearl A.
Purpose: The purpose of the study was to explore experiences of Marshallese adults related to diabetes self-care behaviors during the COVID-19 pandemic. Methods: A qualitative descriptive design was utilized to understand participants' diabetes self-care behaviors during the pandemic. Nine focus groups with 53 participants were held via videoconference and conducted in English, Marshallese, or a mixture of both languages. A priori codes based on diabetes self-care behaviors provided a framework for analyzing and summarizing participant experiences. Results: Both increases and decreases in healthy eating and exercise were described, with improvements in health behaviors attributed to health education messaging via social media. Participants reported increased stress and difficulty monitoring and managing glucose. Difficulty obtaining medication and difficulty seeing their health care provider regularly was reported and attributed to health care provider availability and lack of insurance due to job loss. Conclusions: The study provides significant insight into the reach of health education campaigns via social media and provides important information about the reasons for delays in care, which extend beyond fear of contracting COVID-19 to structural issues.